THE INFLUENCE OF GROWTH OPPORTUNITY, EXPENDITURE AND COMPANY VALUE ON CASH HOLDING IN MINING SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Radiman Radiman; Sri Fitri Wahyuni; Ike Nurjanah (RADJA PUBLIKA, 2022)
The aims of this study are to: (1) find out and analyze the effect of growth opportunity on cash holding, (2) find out and analyze the effect of expenditure on cash holding, (3) find out and analyze the effect of firm value on cash holding, and (4) find out and analyze the growth opportunity, expenditure and company value together have an effect on cash holding. The population in this study are all mining companies listed on the Indonesia Stock Exchange as many as 48 companies and the research sample as many as 8 companies with 5 years of observation. Data collection techniques in this study using documentation techniques. The data analysis technique in this study uses the Classical Assumption Test, Multiple Linear Regression, t-test and F-test, and the Coefficient of Determination.